Living on the edge: Reservoirs facilitate enhanced interactions among generalist and rheophilic fish species in tributaries - Šmejkal, Marek; Bartoň, Daniel; Duras, Jindřich; Horký, Pavel; Muška, Milan; Kubečka, Jan; Pfauserová, Nikola; Tesfaye, Million; Slavík, Ondřej (Frontiers in Environmental Science, 2023)
Most lotic ecosystems have been heavily modified in recent centuries to serve human needs, for example, by building dams to form reservoirs. However, reservoirs have major impacts on freshwater ecosystem functions and severely affect rheophilic fishes. The aim of this review is to gather evidence that aside from direct habitat size reductions due to reservoir construction, competition for food and space and predation from generalist fishes affect rheophilic community compositions in tributaries (river/stream not directly affected by water retention). River fragmentation by reservoirs enables the establishment of generalist species in altered river sections. The settlement of generalist species, which proliferate in reservoirs and replace most of the native fish species formerly present in pristine river, may cause further diversity loss in tributaries. Generalist migrations in tributaries, spanning from tens of metres to kilometres, affect fish communities that have not been directly impacted by reservoir construction. This causes "edge effects" where two distinct fish communities meet. Such interactions temporarily or permanently reduce the effective sizes of available habitats for many native specialized rheophilic fish species. We identified gaps that need to be considered to understand the mechanistic functioning of distinct fauna at habitat edges. We call for detailed temporal telemetry and trophic interaction studies to clarify the mechanisms that drive community changes upstream of reservoirs. Finally, we demonstrate how such knowledge may be used in conservation to protect the remnants of rheophilic fish populations.